Exploration of lived experiences among LGBT individuals living with HIV/AIDS: A phenomenological study - Ikhwan Amirudin; Nor Aziyan; M. Agung Akbar; Agung Waluyo; Astuti Yuni Nursasi (P3M Universitas 'Aisyiyah Surakarta, 2026)
Background: Lesbian, gay, bisexual, and transgender (LGBT) individuals remain a key population with high vulnerability to HIV/AIDS. Although antiretroviral therapy has significantly reduced morbidity and mortality, LGBT people living with HIV/AIDS continue to face layered stigma stemming from both HIV status and sexual or gender identity. However, in-depth understanding of the lived experiences of this population, particularly within Indonesia's sociocultural context, remains limited. Objective: This study aimed to explore and understand the lived experiences of LGBT individuals living with HIV/AIDS in Lampung Province through a phenomenological approach. Methods: A qualitative phenomenological study was conducted with 15 LGBT participants living with HIV/AIDS. Data collection was performed through in-depth interviews during September–October 2025 in Lampung Province. Data analysis employed in vivo coding to preserve the original meaning of participants' expressions. Research reporting followed the Consolidated Criteria for Reporting Qualitative Research (COREQ) guidelines. Results: Analysis yielded three major themes: (1) living in the shadow of layered stigma, (2) negotiating identity and self-acceptance following HIV diagnosis, and (3) building meaning in life and resilience. These themes emerged from interrelated subthemes and categories, all grounded in participants' narratives. Conclusion: The lived experience of LGBT individuals with HIV/AIDS constitutes a complex and multidimensional phenomenon encompassing social, psychological, and existential dimensions. These findings underscore the critical importance of inclusive HIV services that are sensitive to stigma and oriented toward psychosocial needs.